2013
DOI: 10.1021/ja407265p
|View full text |Cite
|
Sign up to set email alerts
|

Proteins in Action: Femtosecond to Millisecond Structural Dynamics of a Photoactive Flavoprotein

Abstract: Living systems are fundamentally dependent on the ability of proteins to respond to external stimuli. The mechanism, the underlying structural dynamics, and the time scales for regulation of this response are central questions in biochemistry. Here we probe the structural dynamics of the BLUF domain found in several photoactive flavoproteins, which is responsible for light activated functions as diverse as phototaxis and gene regulation. Measurements have been made over 10 decades of time (from 100 fs to 1 ms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(141 citation statements)
references
References 44 publications
7
133
1
Order By: Relevance
“…11 Indeed, while most W104 variants undergo the red shift in flavin spectrum, it was shown that W104A AppA is unable to function as competent photoreceptor, 13 consistent with the inability of light excitation to modulate the β-sheet structure in this mutant, 14 and with our own studies using ultrafast time-resolved multiple probe spectroscopy. 15 In addition, W104A recovers the dark state much more rapidly than in the wild-type protein (half-life of 4 sec compared to 15 min). 14 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Indeed, while most W104 variants undergo the red shift in flavin spectrum, it was shown that W104A AppA is unable to function as competent photoreceptor, 13 consistent with the inability of light excitation to modulate the β-sheet structure in this mutant, 14 and with our own studies using ultrafast time-resolved multiple probe spectroscopy. 15 In addition, W104A recovers the dark state much more rapidly than in the wild-type protein (half-life of 4 sec compared to 15 min). 14 …”
Section: Introductionmentioning
confidence: 98%
“…6 A second suggests that direct proton transfer from Y21 to N5 of the flavin occurs. 10 We have proposed that a photoexcitation induced keto-enol tautomerism of the Q63 side chain precedes rotation of this residue, 9,15,16 and have also obtained data that argues against formation of a stable radical intermediate in dAppA. 17,18 …”
Section: Introductionmentioning
confidence: 98%
“…910, 24 Gln rotation may trigger a change in Trp conformation, and we and others have demonstrated that mutagenesis of the Trp uncouples the light-induced changes in the flavin absorption spectrum and hydrogen-bonding from the global changes in BLUF protein structure that accompany photoactivation. 8, 33 …”
Section: Introductionmentioning
confidence: 99%
“…Although it is unknown whether such denaturants as GdmCl and urea induce protein denaturation through the normal folding pathway or via alternate energy wells (42), it is nonetheless useful to demonstrate that the broad distribution of states identified for the NMDA LBD can be reversibly shifted using such methods. Due to both experimental and computational limitations, most protein folding dynamics studies focus on sub-millisecond timescales (55,56), thus we hope the studies presented here also provide guidance on how to combine denaturants with smFRET to understand folding dynamics that occur on longer timescales. Overall, the observed transition statistics provide insight into the relationship between conformational dynamics and function in the NMDAR LBD as well as providing mechanistic detail about the more general topic of protein-folding/unfolding dynamics.…”
Section: Introductionmentioning
confidence: 99%